2018
DOI: 10.1001/jamapediatrics.2017.5314
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multiple Forms of Sexting Behavior Among Youth

Abstract: IMPORTANCEThe existing literature on sexting among youth shows that sexting is a predictor of sexual behavior and may be associated with other health outcomes and risky behaviors. However, there remains a lack of consensus on the prevalence of sexting, which is needed to inform future research, intervention, and policy development.OBJECTIVE To provide a meta-analytic synthesis of studies examining the prevalence of multiple forms of sexting behavior, analyzed by age, sex, geography, and method of sexting.DATA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
376
9
26

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 382 publications
(441 citation statements)
references
References 58 publications
30
376
9
26
Order By: Relevance
“…In relation to specific sexting behavior, it was found that the sending and receiving of text messages with sexual contents were significantly associated with each other (Rice et al, 2014); however, sexting with images was associated with higher rates of sexual activity among at-risk adolescents, more than sending text with explicit sexual contents, also referred to as sexts (Houck et al, 2014). A recent meta-analysis study found that the receiving sexts was more prevalent than the sending of sext messages (Madigan et al, 2018) Adolescents reported sending revealing images either at the request of their girlfriend/boyfriend (Englander, 2012) or to maintain intimacy while they were apart (Drouin et al, 2013). Other motives postulated by researchers include developing one's sexual identity (Van Ouytsel, Van Gool et al, 2017) or merely alleviating boredom (Kopecký, 2012).…”
Section: Sextingmentioning
confidence: 99%
See 4 more Smart Citations
“…In relation to specific sexting behavior, it was found that the sending and receiving of text messages with sexual contents were significantly associated with each other (Rice et al, 2014); however, sexting with images was associated with higher rates of sexual activity among at-risk adolescents, more than sending text with explicit sexual contents, also referred to as sexts (Houck et al, 2014). A recent meta-analysis study found that the receiving sexts was more prevalent than the sending of sext messages (Madigan et al, 2018) Adolescents reported sending revealing images either at the request of their girlfriend/boyfriend (Englander, 2012) or to maintain intimacy while they were apart (Drouin et al, 2013). Other motives postulated by researchers include developing one's sexual identity (Van Ouytsel, Van Gool et al, 2017) or merely alleviating boredom (Kopecký, 2012).…”
Section: Sextingmentioning
confidence: 99%
“…Instant messaging apps that can be used to send images and short clips make sexting easy. Indeed, sexting among celebrities, politicians, and other role models is often exposed in the media (Davidson, 2015); hence, although unfortunate, it is not surprising that adolescents also engage in sexting, despite its possible risks (Madigan et al, 2018;Strassberg et al, 2017). A study of students in grades 6-12 revealed that 17% used sexting; among the 12-year-olds, the rate of use was 3%, and among the 18-year-olds it was 32% (Dake et al, 2012).…”
Section: Sextingmentioning
confidence: 99%
See 3 more Smart Citations